Residual bond behavior between NSM CFRP and concrete at elevated temperatures. (10th October 2020) - Fernandes, B.; Moreno Junior, A.L.; Costa, C.N.
Highlights: Bond behavior between NSM CFRP and concrete after exposure to elevated temperatures was investigated. Beam pullout tests were used to evaluate bond properties. Before reaching Tg, bond properties presented a slight increase, due to post-curing effects. After Tg, bond properties significantly decreased. Semi-empirical model was used to fit experimental values. Abstract: This study evaluated the effect of elevated temperatures on the residual bond (i.e., after cooling) of concrete strengthened with carbon fiber reinforced polymer (CFRP) laminate installed according to the near surface mounted (NSM) technique. Bond was evaluated using the beam pullout test, based on the test method proposed by RILEM RC 05. Initially, tests were conducted at room temperature to determine the influence of bond length. Next, samples were heated at different target temperatures (50 °C to 250 °C). Lastly, bond after heating was evaluated to determine the reduction of bond properties in relation to temperature. In relation to room temperature, higher bond strength was obtained with an anchorage length of 120 mm – the value used for following experimental parts. Regarding the thermal program, it was verified that T g was reached in the resin at the target temperature of 100 °C. Color changes in the resin were observed at the target temperatures of 200 °C and 250 °C. Regarding bond after heating, bond stress varied according to the temperature reached. At 50 °C, before reaching T g, the system presented an increase of 7, 3% in bond strength, mostly due to post-curing promoted by cooling. After that, bond strength significantly decreased, reaching 45, 1% of the initial value at 150 °C.